Il Bildungsroman di August Bournonville: Studi di danza e identità in movimento - Fabris, Rita Maria (Mimesis Journal, 2019)
The case of Nineteenth-century Danish dance history is a relevant field of research both for Cultural Studies on ego-documents and for Dance Studies on dancers’ memoires, because it allows to understand the personal and local experience of the canon of the French danse d’école, in relation to the etical and aesthetic normative pressures of Europe at the time. The paper reconstructs the Bildungsroman of the well-known dancer, coreoghrapher and intellectual August Bournonville (Copenhagen 1805-1879), during his educational years in Paris, in order to analyse its project of identity construction, personal and professional as well as social and institutional, based on the sources collected in the Danish archives and their enactment in the memories and cultural history of dance, both at a local and international level.